Fish-Field Day: Rice-Fish Climate Resilient Demonstration Trial in Wet Season 2024 - Tuy, Sinak; Ouk, Hak (WorldFish, 2024)
The Asian Mega Deltas-Initiative hosted a Farmer Field Day in Takeo Province, showcasing rice-fish farming practices. Over 30 participants observed improved techniques, discussed enhancements for the next season, and six farmers expressed interest in applying these practices, promoting sustainable farming and income generation.